Collectivity in the generation of income and local development: A comparison between Israeli Moshavim and an association of Maria da Fé, Braz - Bianca Siqueira Martins Domingos; Adriana Prest Mattedi; Adilson da Silva Mello; Rosinei Batista Ribeiro (Ciências Sociais Unisinos)
The exercise of thinking about local development involves considering all the complexity of the actors and their interactions in the economic, environmental and social fields in an articulated way. Some of the forms of articulation for income generation are cooperatives and associations that, through collective work and management, give the community and those involved the role of agents. As a way of thinking about local development through collective initiatives for income generation, our aim is to conduct a transnational comparative analysis of rural cooperative Israeli communities, Moshavim, and an Association of Artisans in the municipality of Maria da Fé, in the state of Minas Gerais, Brazil. The methodology took into account the local context of the enterprises, structuring the comparative case study on the basis of the parameters of pluriactivity, rural enterprises, use of natural resources, alternative generation of income, cooperative organization and mutual assistance. The results indicate similarities in the rurality of both, in the use of natural resources and in mutual assistance. The main differences are in the pluriactivity and in the use of manpower (self-labor and wage -labor).